From shade to light : fonio, an african orphan crop, towards renewed challenges - (:unkn) unknown (My University, 2022)
The FAO recently estimated that demand for food will increase by 70% by 2050. The challenge will not only be on increasing the food supply but also on improving its nutritional value under an accelerating rate of environmental and social changes. One solution would be the wider use of underutilized crops to diversify alimentation and develop sustainable and low-input agriculture. Are orphan crops commodities for the future, and how can they be promoted. In this regard, fonio (Digitaria exilis Stapf) appears to be a promising crop. It is an indigenous staple cereal from Western Africa playing a crucial role in food security. Additionally, it is a model crop in important up-to-date concepts such as resilience, agroecology, population health, climatic changes, poverty reduction, and women's empowerment. Nevertheless, fonio has received limited attention from mainstream research compared to other dryland cereals, such as pearl millet and sorghum. Increasingly available genomic resources promise to promote advanced breeding strategies in fonio. This paper presents the past, present, and future of fonio research. We argue the need for interdisciplinarity and multistakeholder research approaches for increasing fonio production, conservation, and sustainable uses.
Keywords: African Research